A Strategy for the Digitalization of Marginalized Communities - Samuel Simbarashe Furusa; Samuel Musungwini; Petros Venganayi Gavai; Melody Maseko (IGI Global, 2023)
The chapter explores the concept of digitalization and digital technology and its importance. The research is based on a systematic literature review, which analyzed articles on digitalization and digital technologies. However, primacy was given to articles on the digitalization of organizations in a marginalized context. The chapter identified the critical success factors and formulation of a digitalization strategy formulation for the transformation of marginalized communities in Zimbabwe. Therefore, the authors highlight the need to explore human-centered digital transformation capabilities and dynamic capabilities in developing countries. The chapter then formulated a strategy for the digitalization of marginalized communities in a developing context.